2005
DOI: 10.1002/mabi.200500142
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Polyanions with Basic Proteins, 2

Abstract: The ability of synthetic polyanions to suppress thermo-aggregation of the oligomeric enzymes (glyceraldehyde-3-phosphate dehydrogenase, lactate dehydrogenase, and aspartate aminotransferase) has been established. The ability of the polyanions to reduce the thermo-aggregation increased in the order poly(methacrylic acid) < poly(acrylic acid) < sodium poly(styrene sulphonate), which agreed well with the increase, in the same order, of the charge density of the chains. The lengthening of the chains, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 22 publications
5
32
0
Order By: Relevance
“…This phenomenon is not so surprising because (i) PEG is a kind of aggregation suppressor, (ii) PEG has the salting-out effect, and (iii) a positively charged polyelectrolyte increases the propensity of repulsion between positively charged proteins. Similar phenomena for protein stabilization have been observed for polyanions complexed with basic proteins [48]. The first point is that PEAMA-g-PEG is the aggregation suppressor of proteins.…”
Section: Stabilization Of Protein By Pegylated Polymersupporting
confidence: 53%
See 1 more Smart Citation
“…This phenomenon is not so surprising because (i) PEG is a kind of aggregation suppressor, (ii) PEG has the salting-out effect, and (iii) a positively charged polyelectrolyte increases the propensity of repulsion between positively charged proteins. Similar phenomena for protein stabilization have been observed for polyanions complexed with basic proteins [48]. The first point is that PEAMA-g-PEG is the aggregation suppressor of proteins.…”
Section: Stabilization Of Protein By Pegylated Polymersupporting
confidence: 53%
“…The enzyme switch by polyelectrolytes has been indicated by Shalova et al [48]. The paper demonstrated that the heat-treated PPC between glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and anionic polymers of poly(methacrylic acid) and sodium poly(styrene sulfonate) was partially reactivated by addition of strong polycation poly(N-ethyl-4-vinyl pyridinium) bromide.…”
Section: Catalytic Activity Switch By Soluble Ppcmentioning
confidence: 88%
“…A molecule of the native enzyme consists of four identi cal subunits and may dissociate into dimers or mono mers, depending on the concentration of GADH and the difficulty of denaturation. As was found, the charge density and the polymerization degree of chains charged negatively [25] or positively [26] and their relative content in mixtures with oppositely charged protein, as well as the pH and ionic strength of solutions, may serve as factors for the effective control of thermal aggregation. Thus, when an oppositely charged high molecular mass polyelectrolyte was added to the enzyme solution in an amount sufficient for the solubilization of protein, the thermal aggrega tion of the enzyme was fully suppressed.…”
Section: Suppression Of Thermal Aggregationmentioning
confidence: 85%
“…During the use of a relatively hydrophobic polystyrene sulfonate anion, which efficiently suppressed the ther mal aggregation of positively charged GADH mole cules, thermal denaturation proceeded deeply and practically irreversibly [25]. An increase in the hydro phobicity of N alkyl groups of poly(N alkyl 4 vinylpyridinium bromides) enhanced the antiaggrega tion activity of polycations with respect to the nega tively charged GADH but simultaneously facilitated the denaturation of the enzyme [26].…”
Section: Suppression Of Thermal Aggregationmentioning
confidence: 96%
See 1 more Smart Citation